2018
DOI: 10.1186/s13049-018-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of civilian patients with suspected traumatic haemorrhage receiving pre-hospital transfusion of packed red blood cells compared to pre-hospital crystalloid

Abstract: BackgroundMajor haemorrhage is a leading cause of mortality following major trauma. Increasingly, Helicopter Emergency Medical Services (HEMS) in the United Kingdom provide pre-hospital transfusion with blood products, although the evidence to support this is equivocal. This study compares mortality for patients with suspected traumatic haemorrhage transfused with pre-hospital packed red blood cells (PRBC) compared to crystalloid.MethodsA single centre retrospective observational cohort study between 1 January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
0
24
1
2
Order By: Relevance
“…However, in six other studies reporting matched or adjusted data, no significant effect on mortality was found, either at 3 hours, 6 hours, 24 hours, 28 days or 30 days post‐infusion, for in‐hospital mortality or overall mortality (Table ). Conversely, Kim et al found significantly lower mortality at 24 hours and a lower mortality overall for patients transfused with both PHT‐plasma and PHTRBC compared with patients receiving PHTRBC only.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, in six other studies reporting matched or adjusted data, no significant effect on mortality was found, either at 3 hours, 6 hours, 24 hours, 28 days or 30 days post‐infusion, for in‐hospital mortality or overall mortality (Table ). Conversely, Kim et al found significantly lower mortality at 24 hours and a lower mortality overall for patients transfused with both PHT‐plasma and PHTRBC compared with patients receiving PHTRBC only.…”
Section: Resultsmentioning
confidence: 98%
“…Five analyses found the RBC requirement in‐hospital or in the first 24 hours to be significantly higher for PHTRBC patients, whereas five others found it to be significantly lower . One of these studies noted that taking the prehospital transfused volume into account, the cumulative 24 hours RBC requirement was not significantly different .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations